Enhancing the Robot PD-Type Feedback Control Performance by Means of Inertial Effects Compensation - Cvejn, Jan; Zapletal, Milan (IEEE (Institute of Electrical and Electronics Engineers), 2020)
The paper describes a modification of the PD-type algorithm with gravity effects compensation for control of robot manipulators, which tries to partially ompensate the influence of inertial terms in the robot motion equations to achieve uniform effect of control on individual axes. In this way it is possible to reduce the overall settling time and to enhance the tracking precision for given magnitude of the control signal, which is demonstrated on a 5-DOF robot example. In comparison to the inverse dynamics method, the influence of non-linear terms in the robot motion equations on total control input is reduced, which helps to increase the control performance and to prevent from reaching the saturation limits. For the basic version of the method asymptotical stability of the control error is proved.
Vylepšení účinnosti zpětnovazebního řízení robota typu PD pomocí kompenzace setrvačných účinků
Keywords: robot manipulator; robot control; PID controller; manipulační robot; řízení robotů; PID regulátor